PERAN MEDIA PEMBELAJARAN DIGITAL QUIZIZZ TERHADAP PENINGKATAN HASIL BELAJAR SISWA SEKOLAH DASAR: ANALISIS STUDI PUSTAKA PERAN MEDIA PEMBELAJARAN DIGITAL QUIZIZZ TERHADAP PENINGKATAN HASIL BELAJAR SISWA SEKOLAH DASAR: ANALISIS STUDI PUSTAKA - Namiera Puzally, Faradhilla; Arwanda Nugraha, Ilham; Dyan Sholehah, Putri; Rahma Risawati, Nur; Ainur Rofiqoh, Jihan; Muhammad Imaduddin; Delia Indrawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has driven innovation in the learning process, including at the elementary school level. However, in practice, learning is often conducted conventionally, resulting in low student engagement and motivation. This study aims to analyze the role of the digital learning medium Quizizz in improving elementary school student learning outcomes. The method used was a literature review, examining various relevant scientific articles from national journals published between 2020 and 2025. Data collection was conducted through documentation, analyzing and comparing research findings related to the use of Quizizz in learning. The study results indicate that using Quizizz can improve student learning outcomes, motivation, and active participation in the learning process. Gamification features such as a points system, leaderboards, and immediate feedback make evaluation activities more engaging and interactive. Furthermore, Quizizz also makes it easier for teachers to monitor student learning progress more effectively. However, the use of this medium still requires adequate internet access and devices for optimal use in learning. Thus, Quizizz can be an effective alternative digital learning medium to support improving the quality of learning in elementary schools.